A Systematic Review of Knowledge, Attitude, and Perception Towards Electroconvulsive Therapy (ECT) in Africa - Abaatyo J; Kaggwa MM (Neuropsychiatric Disease and Treatment)
Joan Abaatyo,1,2 Mark Mohan Kaggwa3,4 1Department of Psychiatry, Uganda Christian University, Kampala, Uganda; 2King Ceasor University, Kampala, Uganda; 3Department of Psychiatry and Behavioural Neurosciences, McMaster University, Ontario, ON, Canada; 4Forensic Psychiatry Program, St Joseph’s Healthcare Hamilton, Ontario, CanadaCorrespondence: Joan Abaatyo, Email joandux@gmail.comBackground: Despite growing evidence showing ECT’s efficacy and efficiency in the management of severe mental health conditions, the knowledge, attitude, and perceptions (KAP) towards ECT vary around the globe. However, KAP guarantees the extent to which ECT is accepted and administered efficiently. This review sheds light on the KAP toward ECT in Africa.Methods: This review included studies that presented results on KAP towards ECT in Africa based on relevant searches from various databases (Ovid, PubMed, Web of Science, and African Journal Online) using appropriate key words from the start until September 2023.Results: Only 13 of the 867 retrieved articles were included in the review. The studies show a reliance on different sources of information, including healthcare professionals, mass media, and the Internet. Moreover, African individuals demonstrated varying levels of knowledge, with many having a limited understanding of ECT. Additionally, attitudes and perceptions toward ECT vary across the continent and depend on exposure and medical qualification.Conclusion: The review of KAP of ECT in Africa reveals a complex landscape characterized by diverse sources of information, varying levels of knowledge among healthcare professionals and students, and a spectrum of attitudes and perceptions towards ECT. The findings underscore the importance of addressing knowledge gaps, dispelling myths, and promoting informed perspectives to enhance the acceptability and utilization of ECT in mental health care.Keywords: electroconvulsive therapy, ECT, knowledge, attitude, perception, Africa